ANALISIS SIKAP MAHASISWA UNIVERSITAS RIAU TERHADAP FENOMENA TRANSGENDER DI JALAN SM. AMIN KELURAHAN SIMPANG BARU KECAMATAN TAMPAN KOTA PEKANBARU - Idwi Ikhsanes; Zahirman Zahirman; Haryono Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is motivated by the existence of transgender at SM. Amin street, Kelurahan Simpang Baru, Kecamatan Tampan, Pekanbaru City. Formulation of the problem in this research are (1) How are student attitudes to transgender phenomenon at Sm.Amin street (2) What is causes student Univeristas Riau choose that attitude (3) How are the action taken by student related attitude who is shown to transgender phenomenon at Sm.Amiin street. This research has purpose to find out the student attitude of Univeristas Riau. This metode of research is descritive and qualitative. Some informan in this research are active students of Universitas Riau that were determind by purposive sampling technique and combined by snowballing sampling technique. Data were collected through interviews, observation and documentation with triangulation technique. Base on research result, it can be concludid that the students of Universitas Riau have negative and positive attitude. The negative attitude with religious, law, health and social reasons. The positive attitude with human rights reason but in essence its human right also have limits that is should not be contradictory with moral, religious values, security, and public order. There are some actions which is shown from some negative attitudes but no action is shown from some positive attitudesKey Word: Attitude, Student Universitas Riau, Transgender Phenomenon